Analisis Kualitas Tidur Pasien Diabetes Melitus Tipe 2 di Wilayah Kerja Puskemas Padang Selasa Kota Palembang - Putri, Ririn Noviyanti; Marlina, Devi; Fatimah, Mustika; Melvani, Rizcita Aprilia; Pertiwi, Kintan Intan (Universitas Batanghari Jambi, 2025)
The aim of this study was to determine environmental factors (sanitation, noise, temperature, lighting) of Type 2 DM patients in the working area of the Padang Tuesday Public Health Center, Palembang City. This research is included in quantitative research with a cross sectional approach. The number of samples in this study was 100 people with an age range of 30-55 years. The results of this study revealed that there was no relationship found between sanitation, noise and lighting and the sleep quality of Type 2 Diabetes Mellitus patients, but the environmental temperature factor could influence the sleep quality of Type 2 Diabetes Mellitus patients in the Padang Tuesday Public Health Center Working Area, Palembang City.